Tissue Adequacy and Diagnostic Yield Assessment in Malignant Lymph Nodes Using Endobronchial Ultrasound (EBUS)-Guided Miniforcep Biopsy vs. EBUS-Guided Transbronchial Needle Aspiration - Pipu Tavornshevin; Poonchavist Chantranuwatana; Vorawut Thanthitaweewat; Virissorn Wongsrichanalai; Thitiwat Sriprasart; Nophol Leelayuwatanakul (Tuberculosis and Respiratory Diseases)
Background Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a predominantly used method for lymph node (LN) metastasis assessment. This study aims to identify tissue adequacy improvement with the addition of EBUS-guided miniforcep biopsy (EBUS-MFB) to EBUS-TBNA in sampling LNs. Methods We assessed tissue adequacy in patients with mediastinal and hilar lymphadenopathy, comparing the combination of EBUS-MFB and EBUS-TBNA with EBUS-TBNA alone. EBUS-MFB was performed with the guide sheath (GS) dilatation technique. Tissue adequacy was a tumor cell count (TCC) of >100 and neoplastic cell neoplastic cell estimate of >25%. Further, we reported the diagnostic yield, tumor cell characteristics, and safety outcomes. Results Among 69 patients (74 nodes), malignant diseases were diagnosed in 41 nodes using both techniques. Tissue adequacy with EBUS-TBNA (93.8% in 30/32 nodes) was comparable with the combined group (96.9% in 31/32 nodes, p=0.317). EBUS-TBNA yielded higher TCC (84.4% with >1,000 cells) than EBUS-MFB (53.1%, p=0.004). The combined approach significantly improved the diagnostic yield in non-malignant diseases compared with EBUS-TBNA alone (97% vs. 78.8%, p=0.014). Of the 32 nodes, 20 demonstrated discordant results between EBUS-TBNA and EBUS-MFB, with EBUS-MFB correctly diagnosing six nodes that EBUS-TBNA misdiagnosed. The complication rate was low (2.9%) with only minor bleeding reported. Conclusion EBUS-TBNA alone and the combination of EBUS-MFB and EBUS-TBNA demonstrated comparable tissue adequacy, with EBUS-TBNA exhibiting better specimen characteristics, potentially sufficient for various molecular analyses. The addition of EBUS-MFB, performed using the GS-dilatation technique, to EBUS-TBNA improved the diagnostic yield and proved to be a safe and efficient approach, particularly in non-malignant diseases.